Sports-wear in wheelchair rugby: establishing design needs - Bragança, Sara (2018)
This paper reports the findings of a preliminary study that intended to understand how wheelchair rugby athletes feel about the clothing they wear while playing the sport and how the available clothes make them feel. 61 non-professional wheelchair rugby players from 21 different teams/clubs in the United Kingdom participated in this study. To understand the players’ opinions, this study consisted of a mixed-method approach, with data collected through a focus group and a questionnaire. The results show that, on top of the lack of availability of sports-wear for this specific sport, which compromises the athletes’ satisfaction, comfort and performance, there is also a need on the part of the athletes for this type of specialized equipment. This study showed that there is a need for this type of sports-wear, hence the importance to act and develop more specialized garments to satisfy this population not just in terms of safety, comfort and performance but also in terms of inclusivity.